Testing the neoclassical migration model: overall and age-group specific results for German regions - Timo Mitze; Janina Reinkowski (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2011)
This paper tests the empirical validity of the neoclassical migration model in predicting German internal migration flows. We estimate static and dynamic migration functions for 97 Spatial Planning Regions between 1996 and 2006 using key labor market signals including income and unemployment differences among a broader set of explanatory variables. In addition to an aggregate specification we also estimate the model for age-group related subsamples. Our results give empirical support for the main transmission channels identified by the neoclassical framework - both at the aggregate level as well as for age-group specific estimates. Thereby, the impact of labor market signals is tested to be of greatestmagnitude for workforce relevant age groups and especially young cohorts between the ages of 18 to 25 and 25 to 30. This latter result emphasizes the prominent role played by labor market conditions in determining internal migration rates of the working population in Germany.
Keywords: R23; C31; C33; 330; Binnenwanderung - Determinanten; Zuwanderung; Abwanderung; Wanderungsmotivation; regionale Faktoren; regionaler Arbeitsmarkt; Arbeitslosenquote; Einkommensunterschied; junge Erwachsene; Erwerbstätige; Siedlungsstruktur; ländlicher Raum; Stadt; Stadtregion; Ballungsraum; Grenzgebiet; Arbeitsmarktgleichgewicht